2008
DOI: 10.1080/02841860701716884
|View full text |Cite
|
Sign up to set email alerts
|

Treatment modelling: The influence of micro-environmental conditions

Abstract: The interest in theoretical modelling of radiation response has grown steadily from a fast method to estimate the gain of new treatment strategies to an individualisation tool that may be used as part of the treatment planning algorithms. While the advantages of biological optimisation of plans are obvious, accurate theoretical models and realistic information about the micro-environmental conditions in tissues are needed.This paper aimed to investigate the clinical implications of taking into consideration th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…This comes as a confirmation of studies showing an improvement of control in experimental systems in the presence of chronically hypoxic cells [64]. In contrast, the presence of acute hypoxia in tumours leads to a worsening of the response to radiation therapy [56, 65, 66]. However, while the fluctuating character of the perfusion disturbances in tumour capillaries does not lead to a full “washout” of the radioresistance of acutely hypoxic cells, the fluctuations are essential for the success of fractionated therapy.…”
Section: Tumour Oxygenation and Treatment Modellingsupporting
confidence: 56%
See 3 more Smart Citations
“…This comes as a confirmation of studies showing an improvement of control in experimental systems in the presence of chronically hypoxic cells [64]. In contrast, the presence of acute hypoxia in tumours leads to a worsening of the response to radiation therapy [56, 65, 66]. However, while the fluctuating character of the perfusion disturbances in tumour capillaries does not lead to a full “washout” of the radioresistance of acutely hypoxic cells, the fluctuations are essential for the success of fractionated therapy.…”
Section: Tumour Oxygenation and Treatment Modellingsupporting
confidence: 56%
“…Experimental studies have shown that chronically hypoxic cells may have low or depleted energy reserves which would impair their repair mechanisms [5255], in contrast with acutely hypoxic cells that are repair competent. Correlating these findings with calculated oxygen distributions in tumours has suggested that the added biochemical sensitisation of chronically hypoxic cells could provide an explanation for the success of radiotherapy, as the chemical radioresistance conferred by hypoxia in general would otherwise require unrealistically high doses to control tumours containing hypoxic cells [49, 50, 56]. This comes as a confirmation of studies showing an improvement of control in experimental systems in the presence of chronically hypoxic cells [64].…”
Section: Tumour Oxygenation and Treatment Modellingmentioning
confidence: 71%
See 2 more Smart Citations
“…In NSCLC, several studies have investigated dose painting based on different tracers such as 18 F‐labeled flurorodeoxyglucose (FDG), fluoromisonidazole (FMISO), and flortanidazole (HX4) . Furthermore, several modeling studies investigated the influence of heterogeneous tumor hypoxia on the treatment outcome . However, given the qualitative information obtained from PET imaging, the determination of the prescribed dose still presents a challenge to the concept of dose painting in general.…”
Section: Discussionmentioning
confidence: 99%